A Reappraisal of Superficial Pleomorphic Liposarcoma: Exploring the Relationship to Atypical Spindle Cell/Pleomorphic Lipomatous Tumor. Issue 3 (11th June 2020) - Berg, Scott Hilliard; Massoud, Cathy Meade; Jackson-Cook, Colleen; Boikos, Sosipatros Alexander; Smith, Steven Christopher; Mochel, Mark Cameron
Abstract: Objectives: Superficial pleomorphic liposarcoma (PL) has a favorable prognosis compared to deeply seated PL. Given developments in the classification of lipomatous neoplasms, we reappraised a series of cases. Methods: Retrospective clinicopathologic evaluation and genome-wide single-nucleotide polymorphism (SNP) microarray studies were performed for cases previously designated superficial PL. Results: Four cases were identified (age, 48-70 years). Two were dermally confined, whereas two were superficial subcutaneous; no recurrences or metastases were reported. Tumors demonstrated pleomorphic spindled morphology with variable cellularity. Multivacuolated atypical lipoblasts were focal in 3 and abundant in 1. Dermal tumors demonstrated atypical cells within sclerotic collagen. Genome-wide SNP microarray studies revealed consistent gains and losses, including losses at the 13q14.2 locus encompassing RB1 and DLEU2 and deletion/disruption of the TP53 locus. Although subcutaneous examples showed genomic changes similar to deep PL, the dermal examples showed fewer genetic alterations, including changes reported in the spectrum of atypical spindle cell/pleomorphic lipomatous tumors (ASPLT). All lacked MDM2 amplification. Conclusions: Careful integration of histologic and genetic features may improve classification of lipomatous neoplasms with atypia, allowing reclassification of some superficial PL as ASPLT.